Pennywise : the story of It [videorecording (Blu-Ray)] - Smart, Gary; Curry, Tim; Thomas, Richard, 1951-; Green, Seth, 1974-; Perkins, Emily, 1977- (Distribution Solutions, 2022)
This behind-the-scenes look at the 1990 mini-series based on Stephen King's novel features interviews with many of the cult classic's key players one of who portrayed the notorious monster clown, Pennywise.